Differentiating Between Mass-forming Chronic Pancreatitis and Pancreatic Ductal Adenocarcinoma: A Challenging Clinical Approach - Zeid, Hadi A; Salfi, Giuseppe; Mansour, Reem; Jardak, Mira N; Khan, Hashim; Abuassi, Mohammad; Boustany, Tara; Onwuzo, Somtochukwu; Boustany, Antoine (International Journal of Clinical Research, 2023)
Introduction: Pancreatic ductal adenocarcinoma (PDAC) is a tumor of the pancreas that has a 5-year survival rate as low as 7.8%. In cases of chronic pancreatitis, it is sometimes challenging to rule out neoplastic changes, as mass-forming pancreatitis (MFCP) that can occur secondary to long-lasting inflammation can commonly mimic the presentation of pancreatic ductal adenocarcinoma. The clinical picture, laboratory, and radiological imaging of PDAC and MFCP may sometimes overlap, resulting in a higher incidence of misdiagnosis and unnecessary surgery. Aim: We aim to describe the various tools available to help physicians distinguish between mass-forming chronic pancreatitis and pancreatic ductal adenocarcinoma. Methods: A literature search was conducted on “PubMed” using the following terms: pancreatic carcinoma, mass-forming chronic pancreatitis, and pancreatic mass. Several articles discussing imaging modalities including ultrasound, CT-scan, and MRI; and laboratory markers including cancer antigen 19–9 (CA 19-9), carcinoembryonic antigen (CEA), glypican-1 (GP-1), low-density lipoprotein receptor (LDLR), and K-RAS, were reviewed. Discussion: Despite their similar presentations, the management of MFCP and PDAC is very different. The similarity in history, clinical symptoms, and imaging findings can lead to unnecessary procedures. In this review, we examined several modalities that physicians might use to avoid any misdiagnosis. Conclusion: Although none of these tests alone has been shown to be superior to the others, a potential suggestion might be to use a combination of these tests to allow a reliable diagnosis.